Peningkatan Kesiapan Siswa dalam Pengambilan Keputusan Rencana Pendidikan dan Karier melalui Asesmen Digital - Nining Anggeraini; Wiwik Wida Farwati; Memy Wardani Elthia; Intan Diva Ivena; Eptina Fatmawati; Nur Alfilail (Unity Academy, 2026)
Choosing an academic major is one of the most important decisions faced by high school students before entering higher education. However, many students experience difficulties in selecting an appropriate study program due to limited information about available majors, career prospects, and an insufficient understanding of their own interests and competencies. This community service program aimed to assist students in identifying their potential and making informed decisions regarding their future study programs through academic major orientation and the use of the Rencanamu.id digital assessment platform. The program employed a participatory educational approach involving 40 twelfth-grade students. Activities included presentations on higher education study programs, career opportunities, and the importance of self-awareness regarding interests and competencies, followed by guided use of the Rencanamu.id platform through interest and personality assessments, as well as participant evaluations. The results indicated that students gained a better understanding of the relationship between their interests, personality traits, competencies, and study program choices. The digital assessment platform helped students identify their potential more objectively and provided recommendations for study programs and career pathways aligned with their profiles. Participants also expressed positive perceptions of the platform, highlighting its ease of use and usefulness in educational planning. These findings suggest that integrating academic major orientation with digital assessment tools can serve as an effective career guidance strategy to support educational decision-making among high school students.